Impact of time and assisted donning on respirator fit. Issue 9 (2nd September 2017) - Rembialkowski, Brian; Sietsema, Margaret; Brosseau, Lisa
ABSTRACT: The goal of this study was to examine the impact of assistance with donning and time on quantitative fit factors (FF) and pass rates for subjects wearing an N95 filtering facepiece respirator (FFR) and a non-certified adhesive mask. Fit factors were measured using two side-by-side TSI Portacount instruments sampling second-by-second simultaneous inside- and outside-facepiece concentrations. Naïve subjects made two visits at least one week apart. At each visit subjects first donned either the respirator or adhesive mask without assistance and performed a five-exercise fast fit test. They then donned a new respirator or mask with assistance in proper donning (e.g., proper forming of the nosepiece, strap placement, etc.) and performed a second five-exercise fast fit test. The same sequence of unassisted and assisted donning was then repeated with the other facepiece. Fifteen subjects participated in the study; time between visits ranged from 7–29 days (average 12 days). On visit 1 the respirator FFs were significantly higher (GM = 88) than for the adhesive mask (GM = 14); with assistance these FFs showed significant improvements to 116 and 124, respectively. At visit 1 almost half of subjects donning the respirator without assistance achieved a passing FF of 100 or greater, while only one-fifth of subjects were able to pass the fit test wearing an adhesive mask without assistance. Pass rates improved for both groups with assistance, but more so for the adhesive mask wearers. On visit 2 the pass rates for both groups had decreased, with the adhesive mask group showing a greater decrease. With assistance, pass rates improved for both groups, but again more so for those wearing the adhesive mask. Results suggest that wearers would benefit from assistance and re-training every time they don a respirator, even if the time between donnings is as short as one or two weeks.